Teachers' Perspectives on Citizenship Education in England - KENAN, SEYFİ (TURKISH EDUCATION ASSOC, 2018)
This study aims to explore the current status of citizenship education in English schools, teachers' understanding of citizenship education, the challenges teachers face and the teaching methods they use to eliminate these challenges in the classroom. The design of this study relies on qualitative research methods where observations in Citizenship classes and interviews with teachers were conducted. The findings from this study suggest that the Science, Technology, Engineering and Mathematics (STEM) subjects have displaced Citizenship and have been weakening it since 2010. Furthermore, the nature of the subject is being challenged by something akin to new Civics and character education in which morality and nationality were more emphasised. Though the priorities have changed for policy makers, they have not completely changed for teachers. It was clear that teachers were doing more than the curriculum required. In the future, conducting more case studies and comparative research on the state of citizenship education in different English schools are suggested.
Keywords: England; The concept of citizenship education; Citizenship; Trained citizenship teacher; Challenges in teaching citizenship; Teaching methods